2020
DOI: 10.1177/0886260520966681
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Being Bullied and Addictive Internet Use Among Chinese Rural Adolescents: The Mediating Effect of Adult Attachment

Abstract: Internet addiction among adolescents is an emerging public health issue. The aim of this study was to examine the relationship between being bullied and internet addiction, and further to test the mediating effect of adult attachments on this relationship among Chinese rural adolescents. A total of 1,270 adolescents from three high schools in Henan province were recruited as subjects. Internet addiction was measured by Young’s internet addiction scale. This study showed that the prevalence of being bullied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…Alcohol use was the common individual characteristic associated with relational, sexual, and property victimization, which is consistent with a study conducted among Italian adolescents (Vieno et al, 2011). Playing video games was associated with sexual and property bullying victimization, which also has been reported in previous studies (Guo et al, 202 ;Ybarra et al, 2014). According to routine activities and lifestyles theories, deviant lifestyles may provide a particularly high chance of victimization because adolescents who engage in deviant activities (such as drinking and being addicted to playing video games) are exposed to deviant peers (Nofziger, 2009).…”
Section: Individual Correlates and Bullying Victimizationsupporting
confidence: 91%
See 2 more Smart Citations
“…Alcohol use was the common individual characteristic associated with relational, sexual, and property victimization, which is consistent with a study conducted among Italian adolescents (Vieno et al, 2011). Playing video games was associated with sexual and property bullying victimization, which also has been reported in previous studies (Guo et al, 202 ;Ybarra et al, 2014). According to routine activities and lifestyles theories, deviant lifestyles may provide a particularly high chance of victimization because adolescents who engage in deviant activities (such as drinking and being addicted to playing video games) are exposed to deviant peers (Nofziger, 2009).…”
Section: Individual Correlates and Bullying Victimizationsupporting
confidence: 91%
“…There are many published studies on bullying victimization in both Western and Eastern countries (Baldry, 2003; Chan & Wong, 2015; Guo et al, 2022; Herráiz & Gutiérrez, 2016; Kim & Kim, 2019; Morales et al, 2019; Obeïd et al, 2020). Researchers have found that there are important differences between Eastern and Western countries in the type of bullying, coping strategies, and attitudes toward bullying, perhaps due to different cultural values and educational systems (Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also supported the direct and positive link between school victimization and Internet addiction ( Guo et al, 2020 ). A longitudinal study indicated that cyberbullying victimization among Spanish adolescents at T1 positively predicted problematic Internet use at T2 ( Gámez-Guadix et al, 2013 ).…”
Section: Introductionmentioning
confidence: 87%
“…Negative Bindungen zu Mutter und Vater waren Prädiktoren für eine Internetsucht, wobei Psychopathologie vor allem in der Bindung zur Mutter interagiert [29]. Unsichere Bindungsmuster sind zudem als Mediatoren in der Beziehung zwischen Bullying und Internetsucht beschrieben [30]. In einer Studie wurde die Entschlossenheit der Eltern als signifikanter Moderator identifiziert, wobei der Effekt dezente Geschlechtsunterschiede zeigte [21].…”
Section: Bindung Und Pathologischer Allgemeiner Internetkonsumunclassified